The Relation of GAFATAR Teachings to Radical Ideology (Law Research Review Quarterly, 2016)
One of the big phenomena that rocked Indonesian society for some time was the unfolding of the Fajar Nusantara Movement (GAFATAR). GAFATAR is an interesting phenomenon because legally, this organization was only established in 2012, but the number of followers has certainly reached thousands. Allegedly, GAFATAR is a continuation of Alqiyadah Al-Islamiyah led by Ahmad Musadeq who several years ago was found guilty of spreading heresy. Because it is considered as a metamorphosis of the heresy, and supported by the facts in the field, the Indonesian Ulema Council (MUI) finally issued a fatwa that the teachings of GAFATAR are heresies that need to be banned. In further development, the Indonesian National Police (Polri) indicated that there were sympathizers radical movements that joined in this GAFATAR. This paper will highlight the relationship between the teachings of GAFATAR and radical movements that can threaten the ideology of Pancasila. This relation, seen when GAFATAR tried to make sense of the country as the Gift of God Semestea Alam.